Penyediaan Akses bagi Penyandang Disabilitas pada Penyelenggaraan Tau-Tau Fest - Fiona; Bagus Githa Adhitya M; Cucu Kurniati (Politeknik Pariwisata NHI Bandung, 2024)
Equality of opportunity in all aspects for persons with disabilities is a fundamental right enshrined in Indonesian legislation and international treaties, namely the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD). One such aspect is participating in arts and cultural activities such as music festivals. Therefore, this research aims to identify the provision of access for persons with disabilities in organizing Tau-Tau Fest, a music festival in Indonesia. The method used is qualitative with data collection techniques in interviews and observation. The results show that although some facilities and services already exist, some aspects require adjustments to meet the needs of people with disabilities, such as viewing areas, queue lines, accessible signage, and staff training on disability awareness. Therefore, recommendations in the form of accessibility plans are given to event organizers and similar music festivals.